PELUANG PENDAPATAN ASLI DAERAH (PAD) SEKTOR PERTAMBANGAN MINYAK DAN GAS BUMI DI ERA OTONOMI DAERAH (Faculty of Social Science, Universitas Negeri Semarang, 2013)
Indonesia is a country rich in natural resources, especially oil and gas. This potential is found in various regions in Indonesia, however, the reality of the oil and gas industry has not fully support national development, especially the development in these areas. Enactment of the Law on Local Government No. 22 of 1999 as amended by Act No. 32 of 2004, brought major changes in Indonesia. Changes that bring Indonesia into a better direction with the formation of a more democratic government, open and pro-autonomy community. System provide the opportunity to participate in managing the area of potential oil and gas wealth of the earth. Law No. 32 of 2004 on Regional Government, among others, regulate relations in the field of resource utilization between the central government and local governments, including the profit sharing on utilization of natural resources and other resources.